A kinetic study on the inhibitory action of sympathomimetic drugs towards photogenerated oxygen active species: The case of phenylephrine - Massad, Walter Alfredo (2005)
Kinetics and mechanism of the aerobic Riboflavin (Rf, vitamin B2) sensitized photodegradation of Phenylephrine (Phen), a phenolamine belonging to the sympathomimetic drugs family, has been studied in water, employing continuous photolysis, polarographic detection of oxygen uptake, steady-state and time-resolved fluorescence spectroscopy, time-resolved IR-phosphorescence and laser flash photolysis. Results indicate the formation of a weak dark complex Rf–Phen, with an apparent association constant of 5.5 ± 0.5 M 1 , only detectable at Phen concentrations much higher than those employed in the photochemical experiments. Under irradiation, an intricate mechanism of competitive reactions operates. Phen quenches excited singlet and triplet states of Rf, with rate constants of 3.33 ± 0.08 and 1.60 ± 0.03 · 109 M 1 s 1 , respectively. With the sympathomimetic drug in a concentration similar to that of dissolved molecular oxygen in water, Phen and oxygen competitively quench triplet excited Rf, generating superoxide radical anion and singlet molecular oxygen (O2( 1 Dg)) by processes initiated by electron- and energy-transfer mechanisms respectively. As a global result, the photodegradation of the vitamin, a known process taking place from its excited triplet state, is retarded, whereas the phenolamine, practically unreactive towards these oxidative species, behaves as a highly efficient physical deactivator of O2( 1 Dg). The phenolamine structure in Phen appears as an excellent scavenger of activated oxygen species, comparatively superior, in kinetic terms, to some commercial phenolic antioxidants.